A VENDOR-BUYER SUPPLY CHAIN MODEL WITH IMPERFECT PRODUCTION UNDER TIME, PRICE AND PRODUCT RELIABILITY DEPENDENT DEMAND - Samanta, Biswarup; Giri, Arpita; Giri, Bibhas C.; Chaudhuri, Kripasindhu (International Journal of Engineering Technologies and Management Research, 2021)
This article investigates a single-vendor single-buyer supply chain model where the market demand depends on time as well as selling price and product reliability. The vendor's production rate is not constant but depends on the market demand. The vendor's production process is not perfectly reliable; it may produce some percentage of defective items during a production run. The vendor takes up a lot-for-lot policy for delivering the ordered quantity to the buyer who performs 100% screening after receiving each lot. The average total profit of the integrated supply chain is derived and a numerical example is taken to validate the developed model. The optimal results of the proposed model are also discussed for some particular cases. Sensitivity analysis is performed to investigate the influence of key model-parameters on the optimal results.